PV/Thermal as Promising Technologies in Buildings : A Comprehensive Review on Exergy Analysis - Kamel, Guedri; Mohamed, Salem; Mamdouh, El Haj Assad; Jaroon, Rungamornrat; Fatimah, Malek Mohsen; Yonis M Yonis, Buswig (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Solar Photovoltaic (PV) systems are degraded in terms of efficiency by increment in their temperature. To keep away from efficiency degradation regarding the temperature increase, various thermal management techniques have been introduced to keep the temperature low. Besides improvement in electrical efficiency, the overall efficiency can be enhanced by using the extracted thermal energy from the cell. The extracted heat in these systems, known as PV/Thermal (PV/T), can be applied for some purposes including water or air heating. This article reviews the works on the PV/T systems exergy analysis and discusses their findings. Based on the findings of the reviewed works, different factors such as the system configuration, used components and elements, and working conditions affect the exergy efficiency of these systems. As an example, use of coolants with improved thermal features, i.e., nanofluids, can cause improvement in the exergy efficiency. In addition to the nanofluid, making use of the thermal energy storage unit can further enhance the exergy efficiency. Furthermore, it has been observed that the materials of nanostructures can be another element that influences the enhancement of exergy efficiency. Moreover, the usage of some components such as glazing can lead to avoidance of thermal energy loss that would be beneficial from an exergy point of view. Finally, according to the reviewed works and knowledge of the authors, some suggestions are represented for future works in this field